2008
DOI: 10.1021/ma702381t
|View full text |Cite
|
Sign up to set email alerts
|

Glassy Dynamics in Thin Polymer Layers Having a Free Upper Interface

Abstract: The molecular dynamics in thin polymer layers having a free upper interface is investigated by means of Broadband Dielectric Spectroscopy and AC-calorimetry. Down to film thicknesses of ∼10 nm no shifts in the average relaxation time and no broadening of the dynamic glass transition are detected for polystyrene, poly(methyl methacrylate), poly(vinyl acetate), poly(γ-benzyl-l-glutamate) and poly(2-vinyl pyridine). This experimental finding restricts to a few nanometers the length-scale of a possible alteration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
104
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 30 publications
(59 reference statements)
20
104
0
Order By: Relevance
“…These features are consistent with the results of dielectric spectroscopy, in which a clear frequency dependence of the glass transition is presented. 21,26 Figure 4 shows the temperature dependence of thickness when the samples were heated at a rate of 0. Figure 7 shows the logarithm of w plotted as a function of reciprocal thickness 1/h.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These features are consistent with the results of dielectric spectroscopy, in which a clear frequency dependence of the glass transition is presented. 21,26 Figure 4 shows the temperature dependence of thickness when the samples were heated at a rate of 0. Figure 7 shows the logarithm of w plotted as a function of reciprocal thickness 1/h.…”
Section: Resultsmentioning
confidence: 99%
“…20 However, such variation of the width of the glass transition was not observed in another dielectric loss study conducted at lower frequencies (0.12 and 0.01 Hz). 21 Ellipsometric measurements taken at various cooling rates for supported PS thin films have revealed that the width of the glass transition is almost independent of film thickness at a fast cooling rate (130 1C min À1 ), whereas measurements taken at slower cooling rates (1 and 3 1C min À1 ) show the width of the glass transition broadening with decreasing thickness. 22 Study of faster dynamics using a calorimeter, with ultrafast heating rates ranging from 1.8Â10 6 to 2.4Â10 6 1C min À1 , has revealed that the width of the transition at this rate becomes broader as the thickness decreases.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent experiments focusing on molecular dynamics in thin polymer layers with a free upper interface revealed no shifts in the average relaxation time and no broadening of the dynamic glass-transition for PS down to film thicknesses of ∼10 nm. 62 Therefore, the decoupling of confinement effects 63 from the change in the solvent content per the area of the polymer film might be necessary. For applications, it is comforting that the total remaining solvent in the polymers remains unchanged over long amounts of time (up to years) if no postproduction treatment is applied.…”
Section: Solvent Enrichment At Polymer/substrate Interfacementioning
confidence: 99%
“…In fact, this is in agreement with what is known in the literature about reorganization and rearrangements of functional groups on polymer surfaces, i.e., it occurs by the exchange and movement of chemical groups between the top surface layers over a distance of only a few nm. [ 30,31 ] Note also that, if the segregation at the particle interface is less than predicted, the minimum thickness of polymer for selfreplenishing may be even smaller.…”
Section: Multiple Self-replenishing: Depth Of Damage and Minimum Polymentioning
confidence: 96%